Renal Endothelial Cytotoxicity Assay to Diagnose and Monitor Renal Transplant Recipients for Anti-Endothelial Antibodies - Lammerts, Rosa G. M.; Born, Jacob van den; Huberts-Kregel, Magdalena; Gomes-Neto, Antonio W.; Daha, Mohammed R.; Hepkema, Bouke G.; Sanders, Jan-Stephan; Pol, Robert A.; Diepstra, Arjan; Berger, Stefan P. (Frontiers in Immunology, 2022)
Tissue-specific nonhuman leukocyte antigen (HLA) antigens can play crucial roles in allograft immunity and have been shown to trigger humoral responses leading to rejection of HLA-matched kidney allografts. Interest in the role of endothelial-specific antigens has grown over the past years, and several case reports have been described in which antibodies reacting with endothelial cells (ECs) are associated with rejection. Such antibodies escape the detection in conventional crossmatch tests as they do not react with lymphocytes. However, due to the heterogeneity of endothelial cells from different vascular beds, it remains difficult to draw organ-specific conclusions from studies describing endothelial crossmatch assays. We present a case of a 69-year-old male patient whose kidney allograft was rejected as hyperacute, despite the absence of pretransplant HLA-specific antibodies. To place findings from previous studies in a kidney-related context, we performed crossmatch assays with primary renal endothelial cells. The patient’s serum was reactive with primary renal ECs, demonstrated by antibody binding and complement-dependent cytotoxicity. Antibodies from this patient did not react with lymphocytes nor were HLA donor-specific antibodies (DSAs) found. Two years later, the patient successfully received a second kidney transplant after treatment with rituximab and plasmapheresis before and after transplantation. We demonstrated that the removal of antibodies against non-HLA EC-specific molecules can be monitored using a primary renal EC crossmatch test, possibly contributing to a successful transplantation outcome.